1995
DOI: 10.1126/science.7624799
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of a G Protein-Activated Human Phosphoinositide-3 Kinase

Abstract: Phosphoinositide-3 kinase activity is implicated in diverse cellular responses triggered by mammalian cell surface receptors and in the regulation of protein sorting in yeast. Receptors with intrinsic and associated tyrosine kinase activity recruit heterodimeric phosphoinositide-3 kinases that consist of p110 catalytic subunits and p85 adaptor molecules containing Src homology 2 (SH2) domains. A phosphoinositide-3 kinase isotype, p110 gamma, was cloned and characterized. The p110 gamma enzyme was activated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
504
3

Year Published

1995
1995
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 651 publications
(518 citation statements)
references
References 30 publications
11
504
3
Order By: Relevance
“…After preliminary screening with phospho-specific antibodies against different signal molecules, we found that the phosphorylation of Akt (Ser473) was consistently elevated in the LNCaP-R273H subline (Figure 1). The data are in agreement with the ability of the Gbg subunits of GPCR to activate PI3K/Akt (Stoyanov et al, 1995;Murga et al, 1998). We noted that a basal level of phospho-Akt was detected in parental LNCaP, presumably due to the inactivating mutation of PTEN in this cell line (Vlietstra et al, 1998).…”
Section: H2-relaxin Induces Activation Of Akt and The Phosphorylationsupporting
confidence: 83%
“…After preliminary screening with phospho-specific antibodies against different signal molecules, we found that the phosphorylation of Akt (Ser473) was consistently elevated in the LNCaP-R273H subline (Figure 1). The data are in agreement with the ability of the Gbg subunits of GPCR to activate PI3K/Akt (Stoyanov et al, 1995;Murga et al, 1998). We noted that a basal level of phospho-Akt was detected in parental LNCaP, presumably due to the inactivating mutation of PTEN in this cell line (Vlietstra et al, 1998).…”
Section: H2-relaxin Induces Activation Of Akt and The Phosphorylationsupporting
confidence: 83%
“…There is a growing awareness that wortmannin inhibits also other types of enzymes apart from PI3-kinase. Elevated levels of phosphatidyl inositol 3,4,5 trisphosphate (PIP 3 ) is seen both as a result of activation of PI3-kinase, and of the G-protein-coupled p110g (Stoyanov et al, 1995). It cannot be excluded that FGFR-1 communicates with G-protein-coupled signal transduction pathways to induce p110g activity, and that wortmannin in our model inhibits p110g and in consequence, cellular migration.…”
Section: Discussionmentioning
confidence: 84%
“…The observed stimulation of the PI-3 kinase and Akt signalling pathway is not necessarily contradictory to the proposed G-protein involvement. Stimulation of G i / G o -protein-coupled receptors may result in activation of PI-3 kinase-γ via its association with the dissociated βγ subunits of the G-protein complex [33,34]. Notably, PI-3 kinase-γ is highly expressed in kidney proximal tubular cells [35].…”
Section: Discussionmentioning
confidence: 99%